To be digital or not to be, that is the ESG question - Luis Martín; Noelia Sánchez-Ortiz (Boletín de Estudios Económicos)
Avoiding global warming and achieving ESG targets requires new vision and new solutions to old problems. Since we are humans, we have to solve challenges with creativity, science and technology. But now, science is not enough, technology is not enough, and creativity is not enough. We live in an interconnected world which has never seen before. And there is a tool to allow this connectivity among stakeholders, without barriers and at a fraction of the cost of any other solution: the digital technology. Cheap, flexible and without boundaries, it is pushing our creativity to the limit. Being open and digital is the only solution in an interconnected world that needs to be open and transparent. An organization intending to measure, improve or report its ESG impact, needs to be digital. Digitalization needs to be introduced in the current and future processes of the industry, which will increasingly rely on digital technologies, allowing collection of data and its use across the company. There is unanimity concerning digitalization, and the need to increase the penetration of digital tools into the company processes so as to improve the organizations efficiency and for reporting purposes. This paper summarises the contexts of ESG requirements, the associated indexes and the digital technologies that can be considered within the organizations. Then, we describe a proposed approach for mapping the status of digitalization of companies and summarise some examples on how digitalization has impacted the ESG impact of relevant organizations.